INTRAUTERINE DEVICE (TCU 380 A): EFFICACY AND COMPLICATIONS AMONG IT'S USERS (ISFAHAN, 1996 - 1997) - B KHANI; F FOROUZESH; M KIEAN POUR; B SOLEIMANI; B JAHANSHAH (Journal of Research in Medical Sciences, 2000)
Introduction. Modern IUDs are as effective as surgical contraception long acting, reversible and medically safe. This study was performed to evaluate efficacy and complications of IUD TCU 380 among users of this IUO in referred women to Isfahan health centers.
Methods. In this study, we inserted IUD TCU 380 A in 767 porous women who get their health cares in Isfahan health centers. They were followed for one year in four visits (1 week, 1, 6 and 12 months after insertion).
Findings. Success rate was 99.3 percent. The most frequent complication was hyper menorrhea (44.4 percent), and the majority of complications occurred 7 to 8 months after IUD insertion. Pap smears were normal in 55.3 percent of women. Removal rate was 13.8 percent and the most frequent cause of it, was hyper menorrhea. Expulsion rate was 3.4 percent and PID was seen in 0.4 percent of them. The major recommended sources for putting IUD were health centers (76.7 percent), and 90 percent of couples were satisfied with this method.
Conclusion. IUD TCU 380 A is safe and effective and represents a suitable contraceptive method for the appropriate patient.